Strategy on Advanced Impact of Implementation of GST on FMCG Sector - Madhu Chakravartula, Dr.S.Rukkumani (International Journal of Advanced Science and Technology, 2020)
The fast-moving consumer goods are our important contributors to both direct and indirect tax. When we look into the GDP (Gross domestic product) contribution, FMCG (Fast Moving Consumer Goods) is an important player. Goods and Service Tax which subsumed most of the indirect taxes in the country would have a significant impact on the fast-moving consumer goods sector. In this paper the advanced impact structure of GST based on FMCG is given to analyze the impact of GST on the companies in the FMCG sector. By using this there will be sustainable growth in GST and reduction in tax evasion. From results it can observe that compared to the GST sector, the advanced impact structure of GST on FMCG sector increase growth in terms of Rank ordering, Awareness and satisfaction of consumers.   Keywords: GST, FMCG, FMCG Distributors, Input Tax Credit (ITC).